Building capacity for knowledge economies in the Arab world: The role of human capital - Al-Roubaie, Amer (International Journal of Engineering and Technology, 2018)
Recent literature on development studies highlights the importance of human capital as a pillar for knowledge creation and innovation. Human capital is a multidimensional concept comprising elements of education, health, income, and social well beings. Unlike other concepts of development which revolve around the traditional factor of production of land, human capital, as an economic input powering sustained economic growth, endows people with technical skills, knowledge and competencies serving to improve employability and increase earnings. The aim of this paper is to discuss the impact of human capital on building capacity to create and sustain knowledge economies in Arab countries. Prospects for the future development of the region will improve commensurate with investment in people and knowledge creation. The current regional development model, centered on the generation of income through resource extraction and channeling investment in large scale real estate projects, misses the mark in terms of generating capacity to sustainably countervail global competition and attain economic benefit from international terms of trade substituting stable high-value-added goods and services for volatile low-value-added equivalents.
Keywords: Human Capital; Arab; Knowledge; Education